Potential chain disaster evolution process of debris flow blockage and dam failure floods in the Bailong River basin - Hongjie LI; Ming CHANG; Liangliang TANG; Gaofneg WANG; Linze LI; Zhe XIA; Xisong ZHU; Zhang NI (地质科技通报)
Objective In the aftermath of the "5.12" Wenchuan earthquake, the frequency of chain disasters, precipitated by debris flow blockages and subsequent breaching floods, significantly increased in the Bailong River basin. The region's distinctive geological conditions, characterized by numerous towns situated on canyon terraces and debris flow accumulation fans, further exacerbate its susceptibility to such chain disasters. This study aims to investigate the potential risks associated with debris flow blockages and flood chain disasters in the Bailong River basin, with a specific focus on the Zhaizi gully debris flow in Bailong River basin, Zhouqu County, Gansu Province. The objective is to elucidate the disaster-breeding characteristics, disaster-inducing conditions, and evolution patterns of the Zhaizi gully debris flow chain disaster, while also delineating the threat range posed by these chain disasters. Methods Through remote sensing interpretation and field surveys, a comprehensive database encompassing the topography, geomorphology, and material sources of the Zhaizi gully debris flow was established. This facilitated the identification of the development characteristics and various physical and mechanical parameters of the debris flow. Using the FLO-2D and HEC-RAS models, numerical simulations were performed under different rainfall frequencies (P=1%, 2%), yielding key parameters such as depth, flow velocity, and the threat range of the debris flow and breaching floods. These parameters facilitated the analysis of hazard intensity and potential risks associated with debris flows and breaching floods. Results Under a 100-year rainfall frequency, the maximum flow velocity of the Zhaizi gully debris flow can reach 11.96 m/s. The average thickness of the debris dam formed is approximately 10 m, leading to complete blockage of the Bailong River and the formation of a dammed lake with a capacity of 6.26 km3. The evolution of the breaching flood lasts approximately 12 hours, with the peak flow occurring about 30 minutes after breach. The impact range of the breaching flood extends from the downstream area of Fengdie Town in Zhouqu County, Gannan, along the main stream of the Bailong River, to the upstream section of Jigan Township in Wudu District, Longnan City, covering an area of 56.36 km2 and spanning a distance of approximately 97.4 km. Based on the simulation results, a preliminary discussion was conducted on a comprehensive risk prevention and control model for basin-wide debris flow disaster chains, integrating monitoring and mitigation measures. Conclusion This study highlights the limitations of traditional models in flood disaster assessment and enhances the understanding of cascading hazards induced by debris flow blockages. The findings provide valuable insights for the risk assessment and engineering design of mitigation projects for similar debris flow disaster chains in the middle and lower reaches of the Bailong River basin.